Cornuside mitigates acute lung injury through suppression of NLRP3 inflammasome-mediated pyroptosis and activation of the Keap1-Nrf2 antioxidant response - Luo, Tong; Liya, Ai; Wang, Feng; Yan, Wei; Chaoketu, Saiyin (Frontiers in Pharmacology, 2025)
IntroductionAcute lung injury (ALI) is a life-threatening respiratory disorder characterized by excessive inflammation and oxidative stress, with no specific pharmacological therapy currently available. Cornuside (CNS), a bioactive iridoid glycoside derived from Cornus officinalis (Sieb. et Zucc.), has garnered increasing attention for its bone-protective, neuroprotective, anti-inflammatory, and anti-diabetic properties, yet its effects on ALI remain unclear.MethodsMale C57BL/6J mice received intratracheal lipopolysaccharide to induce ALI and intragastric CNS (25 or 50 mg/kg) 1 h before and 3 h after LPS. Lung injury was assessed by survival, wet/dry ratio, bronchoalveolar lavage fluid (BALF) protein, histology, and open-field testing. Oxidative stress was evaluated by MPO, MDA, and GSH-PX assays. Keap1-Nrf2 pathway activation was analyzed by Western blot and immunofluorescence of Keap1, Nrf2, GPX4, and NQO1, including Nrf2 nuclear translocation. In vitro, bone-marrow-derived macrophages and J774A.1 cells were used to measure NLRP3 inflammasome activation, caspase-1 cleavage, IL-1β release, and GSDMD-mediated pyroptosis by ELISA, Western blot, confocal imaging, and propidium iodide staining. Lung RNA sequencing identified differentially expressed genes and enriched pathways related to oxidative stress and inflammation.ResultsCNS significantly improved survival, reduced pulmonary edema, and alleviated lung inflammation and locomotor deficits in LPS-challenged mice. Transcriptomic analysis revealed downregulation of oxidative stress- and inflammation-related pathways. CNS inhibited NLRP3 inflammasome activation, as shown by decreased caspase-1 cleavage, IL-1β release, GSDMD processing, and ASC speck formation in vivo and in vitro. In parallel, CNS activated the Keap1-Nrf2 pathway, increasing nuclear Nrf2 translocation and the expression of antioxidant proteins (GPX4, NQO1), while reducing oxidative stress markers MPO and MDA.DiscussionThese findings demonstrate that CNS protects against LPS-induced ALI by concurrently suppressing NLRP3 inflammasome-mediated pyroptosis and enhancing Keap1-Nrf2 antioxidant signaling. This dual mechanism highlights CNS as a promising natural therapeutic candidate for ALI and related oxidative stress-driven lung diseases.